The Potential Role of 5-Methyl-2 (3H)-Furanone in Tamarindus indica as Lipoxygenase (LOX) Inhibitor: in Silico Study - Sulystyaningsih, Sri; Tiring, Natalia Daeng; Bare, Yohanes (Proceeding International Conference on Science and Engineering, 2021)
Abstract. Tamarindus indica is the Fabaceae family that is used in the pharmaceutical theuraphic because it contains polyphenols. One of the studies is to have anti-inflammatory properties. When inflammation occurs, , the lipoxygenase (LOX) pathway will be formed as a mediator of acute inflammation. Reducing inflammation, it is necessary to control genes that play a role in increasing inflammation, one of which is LOX. This study aims to analyze the potential of the 5-Methyl-2 (3H)-Furanone compound on LOX action. The compound 5-Methyl-2 (3H) -Furanone (CID 11559) was downloaded from the PubChem database. The 5-LOX protein was downloaded from Protein Data Bank (PDB 6N2W) and and prepared by removing ligands and molecules that bind to Discovery Studio V19.1.0.18287. The compounds and proteins were interacted with the Vina autodock software integrated in the PyRX software and analyzed using Discovery Studio V19.1.0.18287. The results showed 5-Methyl-2 (3H) -Furanone binds to lipoxygenase on the active sites of Gln329, Arg518, Ile330, Leu153, Glu146, Asn328, and Asp290. The three bioactive compounds tamarin bind to lipoxygenase with hydrogen, hydrophobic and van der Waals forces. The ligands and proteins that are formed produce energy -6Kcal/mol. The interactions that occur between compounds contained in Tamarindus indica have potential as inhibitors of LOX and are predicted to be used as compounds for inflammatory therapy.